A Disparity of Youngsters’ Fitness among Girl Students in the Public Campuses ofTerai Region, Nepal (Interdisciplinary Research in Education, 2021)
The objective of this paper presents to compare the disparity of youngsters’ fitness among girl students between Saptagandaki and Nav Kshitiz public campuses of Terai region, Nepal. It hypothesized that there is significance difference between them. Among test items of AAHPER standing broad jump, shuttle run and sit-ups (flexed leg) have applied as tool of this paper. Altogether 40 youngsters’ girls were the respondents, whereas 20 students from each campus designated through multistage sampling method. While comparison to the mean scores of Nav Kshitiz youngsters, the Saptagandaki youngsters found better fitness in all three test scores as well as composite score. Furthermore it applied p-value of t-test, there were found significance difference in the youngsters’ fitness scores an overall test items between both groups. Hence, hypothesis is accepted. In comparison to the Nav Kshitiz youngsters, the Saptagandaki youngsters have more involved in the physical works and sporting activities.